2017
DOI: 10.1039/c7ja00242d
|View full text |Cite
|
Sign up to set email alerts
|

Computational model of a direct current glow discharge used as an ambient desorption/ionization source for mass spectrometry

Abstract: A new model of a plasma ionization source anchored by experimental data giving a comprehensive view of the discharge mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In contrast, charge transfer reagent species were most abundant at low gas flow rates (0.5 L/min) and high discharge currents (30 mA). Considering the extreme cases of 0.5 L/min and 30 mA, or 1.5 L/min and 5 mA, while the condition used in our study (1.5 L/min and 25 mA) is more intermediate and is reported as a typical operating condition of the FAPA source, we may indeed expect to have both PT and CT reagent ions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, charge transfer reagent species were most abundant at low gas flow rates (0.5 L/min) and high discharge currents (30 mA). Considering the extreme cases of 0.5 L/min and 30 mA, or 1.5 L/min and 5 mA, while the condition used in our study (1.5 L/min and 25 mA) is more intermediate and is reported as a typical operating condition of the FAPA source, we may indeed expect to have both PT and CT reagent ions.…”
Section: Resultsmentioning
confidence: 99%
“…This yields ca. 11.25 W applied power, as reported in both experimental and computational studies for a typical FAPA source. , The helium gas can flow out of the discharge cell through an orifice with 1 mm diameter in the center of the disk electrode. Details of the geometry and operating conditions are summarized in Table S1 in the Supporting Information (SI).…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through modeling studies, 25,39 the He 2 + ion was identified as one of the key species for ADI-MS ionization; it yields N 2 + and H 2 O + , which are important primary reagent ions leading to the formation of protonated water-cluster ions (i.e., [H 2 O] n H + ) that are in turn responsible for proton transfer ionization. The closeness in the behavior of He and N 2 + emission is clear in Fig.…”
Section: Two-dimensional Images Of Steady-state Ltp Emissionmentioning
confidence: 99%